Comparative Sequence Analysis of Historic and Current Porcine Rotavirus C Strains and Their Pathogenesis in 3-Day-Old and 3-Week-Old Piglets - Chepngeno, Juliet; Takanashi, Sayaka; Diaz, Annika; Michael, Husheem; Paim, Francine C.; Rahe, Michael C.; Hayes, Jeffrey R.; Baker, Courtney; Marthaler, Douglas; Saif, Linda J.; Vlasova, Anastasia N. (Frontiers in Microbiology, 2020)
The increased prevalence of porcine group C rotavirus (PRVC) in suckling piglets and the emergence of new genetically distinct PRVC strains are concerning due to the associated significant economic losses they cause to the swine industry. We sequence genomes sequence analyzed two new PRVC strains, RV0104 (G3) and RV0143 (G6) and compared their pathogenesis with that of the historic strain Cowden (G1) in gnotobiotic (Gn) pigs. Near complete genome sequence analysis (~50% of the RV0104 VP4 gene missing) confirmed that these two strains were distinct from one another and the Cowden strain. However, the RV0104 and RV0143 VP4 genes shared very high nucleotide identity (98.7%) but were distinct from Cowden. VP1, VP2, VP6, NSP1-NSP3 and NSP5 genes were more similar between Cowden and RV0143, whereas VP3, VP4, VP7 and NSP4 shared higher nucleotide identity between Cowden and RV0104. Three-day-old and 3-week-old Gn piglets were inoculated with 105 FFU/ml of Cowden, RV0104 or RV0143, or mock. All 3-day-old piglets developed severe diarrhea, anorexia and lethargy, with mean PRVC fecal shedding titers peaking and numerically higher in RV0104 and RV0143 piglets on post infection day (PID) 2. Histopathological examination of the small intestine revealed that the 3-day-old Cowden and RV0104 inoculated piglets were mildly affected, while significant destruction of small intestinal villi was observed in the RV0143 inoculated piglets. Consistent with the highest degree of pathological changes in the small intestines, the RV0143 inoculated piglets had numerically higher levels of serum IL-17 and IFN-α cytokines and numerically lower PRVC IgA geometric mean antibody titers. Milder pathological changes and overall higher titers of PRVC IgA antibodies were observed in 3-week-old vs. 3-day-old piglets. Additionally, diarrhea was only observed in RV0104 and RV0143 (but not Cowden) inoculated 3-week-old piglets, while levels of serum IL-10 and PRVC IgA antibodies were higher in Cowden inoculated pigs, consistent with the lack of diarrhea. Thus, we confirmed that these current, genetically heterogeneous PRVC strains possess distinct pathobiological characteristics that may contribute to the increased prevalence of PRVC diarrhea in neonatal suckling piglets.